Management and industry case studies in UK industrial history - Wilson, John F. 1955-; Wong, Nicholas; Toms, Steven (Routledge focus on industrial history, 2020)
This shortform book presents key peer-reviewed research selected by expert series editors and contextualised by new analysis from each author on how the specific field addressed has evolved. With contributions on the historic turn' in management studies, workers' rights, occupational health, industrial networks and the development of the organisation, practices and principles of large UK businesses, this volume provides an array of fascinating insights into industrial history. Of interest to business and economic historians, this shortform book also provides analysis and illustrative case-studies that will be valuable reading across the social sciences